Dramatic response of refractory metastatic squamous cell carcinoma of the skin with cetuximab/pembrolizumab. (May 2021) - Hober, Candice; Jamme, Philippe; Desmedt, Eve; Greliak, Anna; Mortier, Laurent
Cutaneous squamous cell carcinoma (cSCC) accounts for 20% of skin cancers. At an advanced stage the prognosis is poor, making cSCC the second leading cause of death from skin cancer. In cases of metastatic or unresectable disease, anti-programmed cell death 1 (anti-PD1) treatment has shown promising results in a recent phase II study. Although anti-PD1 treatment now offers higher response rates, the responses remain inconsistent and may lead to therapeutic impasses. Preclinical data have suggested synergy between anti-epidermal growth factor receptor (anti-EGFR) and immunotherapy. We report the case of a patient with metastatic cSCC that proved refractory first to anti-EGFR/carboplatin and then to immunotherapy, but who showed a complete and durable response with cetuximab/pembrolizumab combination. This response could reflect synergy of the two treatments.